Transformasi Digital dalam Pelayanan Publik: Analisis Implementasi Aplikasi PRO Denpasar Sebagai Model E-Government di Indonesia - Maliki Aji Prakoso; Senna Wahyu Aji; Aji Ryandana; Rio Febrian; Rico Widit (Public Service and Governance Journal, 2025)
Digitization has driven information technology to become a fundamental foundation in facilitating human tasks across various aspects, including governance. This study focuses on the implementation of the Online Public Service Application (PRO) Denpasar as part of e-government implementation in Denpasar City. The research aims to analyze the effectiveness of the PRO Denpasar application in improving the quality of public services, identify implementation challenges, and formulate improvement strategies based on a SWOT analysis. This study employs a descriptive qualitative method as the issues examined are social and dynamic in nature. This method enables researchers to explore phenomena in-depth by gathering information from various perspectives. The qualitative approach provides flexibility in understanding the social context and the dynamics of interactions between individuals or groups related to the phenomenon being studied. The results indicate that although the public satisfaction level with the application exceeds 80%, several challenges remain, such as uneven socialization, digital divides, and slow responses from relevant parties. The proposed strategies include developing a collaboration-based digital platform, enhancing data security, and implementing digital inclusion programs. This research underscores the importance of multi-stakeholder collaboration and continuous innovation to support the success of e-government.